1975
DOI: 10.1073/pnas.72.7.2691
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin architecture: investigation of a subunit of chromatin by dark field electron microscopy.

Abstract: Dark field scanning electron microscopy of unstained, unfixed samples of chromatin, histone-l-depleted chromatin, and nucleohistone has been used to identify an apparent subunit of chromatin, namely a disk-shaped structure we term the unit particle, which is probably about 135 A wide and 50 A thick in the hydrated state. The unit particles are found at rather uniform intervals along thin DNA-like fibers. Histone 1 depletion leads to a bimodal distribution of these spacings. Our observations suggest that the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…One turn was measured to consist of 83 ± 4 base pairs (Fig. 7) which is in accord with models proposed previously (22,23,43,44). Hence, these results are consistent with those obtained by DNase II digestion.…”
Section: Discussionsupporting
confidence: 81%
“…One turn was measured to consist of 83 ± 4 base pairs (Fig. 7) which is in accord with models proposed previously (22,23,43,44). Hence, these results are consistent with those obtained by DNase II digestion.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the shape of the nucleosome core is more nearly a short cylinder than a sphere. This conclusion is in agreement with recent reports (27)(28)(29) …”
supporting
confidence: 94%
“…3, a and b). In the projections observed most frequently, the characteristic concentration of the stain in the middle of the circular nucleosomes (25,28,31) was clearly visible (Fig. 3b), an indication that in this projection one is looking through rows of superimposed nucleosomes.…”
Section: Hexagonal Crystalsmentioning
confidence: 87%
“…Eukaryotic chromosomes are composed of chromatin fibres which themselves consist of unit structures (Watanabe et d., 1990), nucleosomes of 10-15nm diameter (Langmore & Wooley, 1975;Oudet et al, 1975) and superbeads of 15-5Onm diameter (Hozier et d., 1977;Azorin et al, 1982;Zentgraf & Franke, 1984). Bordas et d. (1986) have shown that the native uncondensed chromatin fibre in solution has an outer diameter of c. 30 nm using synchrotron radiation scattering analysis.…”
Section: Introductionmentioning
confidence: 99%